A fuzzy 'boater' model to detect fouling and spreading risk of non-indigenous species by recreational boats. (1st November 2016) - Ferrario, Jasmine; Marchini, Agnese; Borrelli, Paola; Gigli Berzolari, Francesca; Occhipinti-Ambrogi, Anna
Abstract: Recreational boating is an unregulated and underestimated vector of spread of non-indigenous species (NIS) in marine environments. The risk of a single boat to spread NIS depends not only on the local environmental context, but also on the type of boat and on the boat owner's behaviour (hull cleaning and painting frequency, travel history). In this paper we present a model to assess the risk of fouling and spreading of NIS and its application to data derived from a questionnaire given to Italian boat owners. The model uses a two-levels fuzzy logic approach: (1) the first level assesses the risk of hull fouling and risk of spreading separately; (2) the second level combines the two separate risks in an overall index ranging from 0 (null risk) to 100 (highest risk) and measures the global risk of NIS introduction and spread through recreational boating. The questionnaire and the fuzzy model allow for a simple and rapid assessment of boats most likely to be infested. The proposed fuzzy model can be easily edited and adapted to context-specific ecological and social conditions. The results of this Italian study showed that 53.9% of the respondents were in the very-low and low risk categories, and 46.1% in the medium, high and very-high risk categories. Possible associations between some boaters habits and the fouling and spreading risk were explored using logistic regression analyses. The results indicate a high-risk profile of boat owner as an experienced sailor who visits many marinas during the summer season. Biosecurity guidelines, containment measures and awareness raising programmes should be implemented to prevent and avoid further spread of NIS in marine environments, and such management actions would benefit from the early detection of high-risk boats, and from the identification of profiles of boaters upon which these initiatives should be prioritized. Graphical abstract: Highlights: We present a model to assess risk of non-indigenous species introduction by boating. The model uses a fuzzy logic approach and questionnaire data as input. The model was applied on 193 Italian boaters, of which 46% had a medium-high risk. The high-risk profile corresponds to an expert sailor visiting different marinas. We observed low awareness of boaters on hull fouling as a vector of introduction.